2013
DOI: 10.1007/s12199-013-0337-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subjective symptoms and allergy state among medical students exposed to low-level formaldehyde 6 months after completion of a gross anatomy dissection course

Abstract: Objectives Our purpose was to clarify whether subjective symptoms of low-level formaldehyde (FA) exposure in medical students were transient or persistent and to investigate whether the allergy state changed as a result of exposure. Methods We surveyed the prevalence of medical students' subjective symptoms and their allergy state before, during, and 6 months after completion of a gross anatomy dissection course by using two self-administrative questionnaires. Students completed the first survey at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
4
10
0
Order By: Relevance
“…In a recent study in Thailand, about FA exposure in Anatomy labs, most students also had these symptoms [7]. Similar results were found in the studies of [4, 13,15,21], which reported, in addition to these clinical symptoms, general fatigue and skin irritation.…”
Section: Discussionsupporting
confidence: 78%
“…In a recent study in Thailand, about FA exposure in Anatomy labs, most students also had these symptoms [7]. Similar results were found in the studies of [4, 13,15,21], which reported, in addition to these clinical symptoms, general fatigue and skin irritation.…”
Section: Discussionsupporting
confidence: 78%
“…After the repair work, the number of individuals with subjective symptoms significantly decreased in 2011; however, not all symptoms disappeared [11]. There are very few studies that have assessed the health effects of exposure to post-repair FA levels on medical students and experimental animals with the exception of our previous studies [11,12]. Therefore, it is necessary to continue measuring the indoor FA concentrations and devise further strategies aimed at reducing exposure to FA even in an environment of low FA levels within the exposure limits set by the Japan Society for Occupational Health (0.1 ppm) [13].…”
Section: Introductionmentioning
confidence: 83%
“…Previously published data have shown clinical symptoms formaldehyde exposure of medical students and instructors in the anatomy laboratory (3,9,11,12,13,14,15,16,17,18,19,20,21,22,30,31).…”
Section: Discussionmentioning
confidence: 98%
“…Formaldehyde may function as an irritant and cause mild eye and mucous membrane complaints at air levels of 0.5-2 ppm (8). Different studies related to formaldehyde concentrations in the air and clinical symptoms are presented in Table 1 (14) Inhalation exposure Gross anatomy dissection course -During the course were eye fatigue, runny nose, and dry eyes. Most symptom after the course was eye fatigue.…”
Section: Clinical Symptomsmentioning
confidence: 99%
See 1 more Smart Citation